Intrinsic and extrinsic drivers of succession: effects of habitat age and season on an aquatic insect community. (16th April 2014) - MURRELL, EBONY G.; IVES, ANTHONY R.; JULIANO, STEVEN A.
<x xml:space="preserve">Abstract</x> 1. Classic studies of succession, largely dominated by plant community studies, focus on intrinsic drivers of change in community composition, such as inter‐specific competition and changes to the abiotic environment. They often do not consider extrinsic drivers of colonisation, such as seasonal phenology, that can affect community change. 2. Both intrinsic and extrinsic drivers of succession for dipteran communities that occupy ephemeral pools, such as those in artificial containers were investigated. By initiating communities at different times in the season and following them over time, the relative importance of intrinsic (i.e. habitat age) versus extrinsic (i.e. seasonal phenology) drivers of succession were compared. 3. Water‐filled artificial containers were placed in a deciduous forest with 20 containers initiated in each of 3 months. Containers were sampled weekly to assess community composition. Repeated‐measures mixed‐effects analysis of community correspondence analysis (CA) scores enabled us to partition intrinsic and extrinsic effects on succession. Covariates of temperature and precipitation were also tested. 4. Community trajectories (as defined by CA) differed significantly with habitat age and season, indicating that both intrinsic and extrinsic effects influence succession patterns. Comparisons of Akaike Information Criteria corrected for sample sizes (AICcs) showed that habitat age was more important than season for species composition. Temperature and precipitation did not explain composition changes beyond those explained by habitat age and season. 5. Quantification of relative strengths of intrinsic and extrinsic effects on succession in dipteran and other ephemeral communities enables us to disentangle processes that must be understood for predicting changes in community composition.